PERBANDINGAN KUALITAS PRODUK DAN MINAT MENABUNG PADA LPD DESA ADAT TAJUN DENGAN DESA ADAT TEGAL - Eka Swarnadi Luh; Ketut Budi Susrusa; Ida Ayu Listia Dewi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
LPDs are non-bank financial institutions that are regulated and approved by the Regional Regulations of the Province of Bali. The management of LPD is fully handed over to the relevant Pakraman village. In line with the rapid development of LPDs, it turns out that on the other hand it shows diverse performance, so that LPDs need to pay attention to the level of product quality and customer interest in the products offered.            The purpose of the study was to determine the comparison of product quality and interest in saving at the Tajun Traditional Village LPD with the Traditional Village of Tegal. The number of samples from Tajun Adat Village LPD was 98 people and the LPD of Tegal Traditional Village was 84 people. The research data were analyzed by the Mann-Whitney Test. The results showed that there was a significant difference between the quality of the products of the Adat Village of Tajun LPD and the Traditional Village of Tegal. This difference is indicated by indicators of physical evidence, reliability, responsiveness and empathy. The product quality of Tajun Adat Village's LPD is better than the traditional village of Tegal. There is a significant difference between the interest in saving the traditional village of Tajun LPD and the traditional village of Tegal. The difference is in the indicator of confidence. Interest in Saving Tajun Indigenous Village LPD is higher than the Traditional Village of Tegal.